Animal abuse in Colombia: criminal and infringement protection in favor of animals - Pérez Arias, Luz Marcela; Monsalve Mantilla, Milton Duban (DIXI, 2020)
Objectives: Look for points of intersection between criminal law and the infringement regime, clarifying the differences that exist and the objectives and purposes of each norm. Methodology: Through a documentary analysis, it investigates the main modifications introduced in each of the statutes, reviewing the jurisprudence and going to the analysis of sources. Findings: In Colombia, when dealing with cases of “animal abuse”, there is an infringement regime of knowledge of the Police Inspections and Municipal Mayors, which is supported by Law 84 of 1989 and the National Police and Coexistence Code; in turn, the criminal procedure is in charge of municipal criminal judges in accordance with Law 1774 of 2016, which is why it is pertinent to study its various implications. Conclusions: Law 1774 of 2016 created a criminal instance and at the same time strengthened sanctions of the police or infringement law. Both Law 1774 of 2016 (Law of Animal Abuse), and Law 1801 of 2016 (or National Police and Coexistence Code) represent an advance for the protection, conservation and recognition of animals as “subjects of rights”, leaving behind the “objectifying” vision, typical of the Civil Code.